THE CONCEPT OF MOHAMMAD NATSIR'S NATIONAL DAKWAH AND ITS IMPLEMENTATION IN THE INTEGRITY OF THE NKRI - Madeni; Abdul Hamid; Zamakhsyari Abdul Majid (Jurnal Bina Ummat: Membina dan Membentengi Ummat, 2023)
ABSTRACT Dissertation with the title Mohammad Natsir's Concept of National Da'wah and Its Implementation in the Integrity of the Republic of Indonesia. Written by Madeni. The background of this research is based on the emergence of various problems in society, there are thoughts that want to clash between Islam and Indonesianism, that want to clash between Pancasila and Islam, between Islam and government. Therefore, this research will examine and explore Mohammad Natsir's concept of national da'wah and its implementation in the Unitary State of the Republic of Indonesia (NKRI). The aim of this research is to explore the concept of national da'wah put forward by Mohammad Natsir and to find out the implementation of the concept of national da'wah in the integrity of the Republic of Indonesia, as well as to find out the supporters and obstacles to the implementation of Mohammad Natsir's concept of national da'wah. This research method uses a qualitative research method in the form of a literature study with a text analysis approach. Data collection for this research was carried out through documentation by reviewing books and works written by Mohammad Natsir. The results of this research found that; Mohammad Natsir's concept of national dakwah is the Concept of National Da'wah Integrity which combines six important pillars, namely: Maintaining Islam as the basis of the state, Maintaining the integrity of the Republic of Indonesia, Maintaining unity and integrity, Maintaining tolerance and love for the homeland, Maintaining collaboration between individuals and elements of society. Meanwhile, its implementation in the current era can include the following aspects: Instilling National Values: Strengthening Inter-Religious Harmony, Maintaining National Identity, Strengthening Social Unity and Justice, Active Involvement in Nation Building. Meanwhile, the concrete steps taken by Mohammad Natsir are as follows: Da'wah against secularism, Forming educational and da'wah institutions, Political Da'wah activities, Participation in nation building, Active in Islamic organizations. The obstacles and challenges are as follows: Religious, ethnic and cultural differences. Identity politics that are exclusive and do not respect differences can trigger social conflict and affect the national spirit. Social and economic disparities and developments in technology and information